Genotyping of vibrio cholerae non-O1 isolates using enterobacterial repetitive intergenic consensus-polymerase chain reaction (eric-pcr) - Annya, anak Ambrose. (Universiti Malaysia Sarawak, (UNIMAS), 2005)
A total of 30 V. cholerae non-O 1 isolates from river and shrimp pond were identified based on biochemical tests, followed by species-specific Polymerase Chain Reaction (PCR) targeting the outer membrane protein W (ompW) gene for molecular confirmation. All 30 V. cholerae non-01 isolates produced amplified products of 588 base pair (bp). Next, one set of primers (ERIC-R and ERIC-F) were used to assess the genetic relatedness among the 30 V. cholerae non-O 1 isolated using Enterobacterial Repetitive Intergenic ConsensusPolymerase Chain Reaction (ERIC-PCR). A total of27 fingerprint patterns (FPs) with bands ranging in sizes from 0.3 kbp to 5.0 kbp were generated in all the V. cholerae non-01 isolates. The ERIC profiles were further analyzed to establish the genetic relationship between the isolates through the construction of a dendrogram. The dendrogram is comprised of four sub-clonal clusters where it was observed that isolates from different origin tended to group together in the same clusters. Different genetic patterns that were produced among the isolates showed that ERIC-PCR is able to identify the genetic variations of the V. cholerae isolates up to subspecies level. Based on these results, ERIC-PCR had proven to be a rapid and reliable method to study the genetic relatedness of V. cholerae isolates from different location.